Cutting Force in Stone Machining by Diamond Disk. (28th November 2010) - Turchetta, S.
Abstract : Stone machining by diamond disk is a widespread process to manufacture standard products, such as tiles, slabs, and kerbs. Cutting force and energy may be used to monitor stone machining. Empirical models are required to guide the selection of cutting conditions. In this paper, the effects of cutting conditions on cutting force and cutting energy are related to the shape of the idealized chip thickness. The empirical models developed in this paper can be used to predict the variation of the cutting energy. Therefore these models can be used to guide the selection of cutting conditions. The chip generation and removal process has been quantified with the intention of assisting both the toolmaker and the stonemason in optimising the tool composition and cutting process parameters, respectively.